Production of drug nanosuspensions: effect of drug physical properties on nanosizing efficiency. (1st February 2018) - Liu, Tao; Müller, Rainer H.; Möschwitzer, Jan P.
Abstract: Objective: Drug nanosuspension is one of the established methods to improve the bioavailability of poorly soluble drugs. Drug physical properties aspect (morphology, solid state, starting size et al) is a critical parameter determining the production efficiency. Some drug modification approaches such as spray-drying were proved to improve the millability of drug powders. However, the mechanism behind those improved performances is unclear. This study is to systematically investigate the influence of those physical properties. Methods: Five different APIs (active pharmaceutical ingredients) with different millabilities, i.e. resveratrol, hesperetin, glibenclamide, rutin, and quercetin, were processed by standard high pressure homogenization (HPH), wet bead milling (WBM), and a combinative method of spray-drying and HPH. Results: Smaller starting sizes of certain APIs could accelerate the particle size reduction velocity during both HPH and WBM processes. Spherical particles were observed for almost all spray-dried powders (except spray-dried hesperetin) after spray-drying. The crystallinity of some spray-dried samples such as rutin and glibenclamide became much lower than their corresponding unmodified powders. Almost all spray-dried drug powders after HPH processes could lead to smaller nanocrystal particle size than unmodified APIs. Conclusion: The modified microstructure instead of solid state after spray-drying explained the potential reason for improved nanosizing efficiency. In addition, the contribution of starting size on the production efficiency was also critical according to both HPH and WBM results.